2014
DOI: 10.4322/floram.2014.015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de Variáveis Climáticas no Crescimento Mensal de Pinus taeda e Araucaria angustifolia em Fase Juvenil

Abstract: RESUMOO objetivo deste trabalho foi construir curvas de produção e de incremento corrente mensal (ICM), e analisar o efeito de variáveis climáticas no crescimento mensal em diâmetro e altura de Pinus taeda L. e Araucaria angustifolia (Bert.) O. Kuntze, no período de três anos, em fase juvenil. Para tanto, foram selecionadas 30 árvores de cada espécie, sendo, mensalmente, entre junho de 2006 e julho de 2009, medidas as variáveis diâmetro e altura. As variáveis climáticas são provenientes de duas estações meteor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
1
6
1
10
Order By: Relevance
“…Similarly, Machado et al (2014) verified mean cumulative growth in height of 1.1 m year -1 for planting aged 3 years. In the present study, we observed that growth in height remained constant until 74 months, without evidence of growth spurts from third year after planting, regardless propagation method (Carvalho, 2003), and of 1.1 m year -1 (Machado et al, 2014), is possibly related to low site fertility of experimental area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Machado et al (2014) verified mean cumulative growth in height of 1.1 m year -1 for planting aged 3 years. In the present study, we observed that growth in height remained constant until 74 months, without evidence of growth spurts from third year after planting, regardless propagation method (Carvalho, 2003), and of 1.1 m year -1 (Machado et al, 2014), is possibly related to low site fertility of experimental area.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Machado et al (2014) verified mean cumulative growth in height of 1.1 m year -1 for planting aged 3 years. In the present study, we observed that growth in height remained constant until 74 months, without evidence of growth spurts from third year after planting, regardless propagation method (Carvalho, 2003), and of 1.1 m year -1 (Machado et al, 2014), is possibly related to low site fertility of experimental area. This hypothesis is supported by the fact that Araucaria is a demanding species in relation to soil conditions, especially regarding depth (Puchalski et al, 2006) and nutrient availability (Golfari, 1971, Schneider et al;1992, Carvalho, 2003.…”
Section: Discussionmentioning
confidence: 99%
“…in a mixed ombrophilous alluvial forest in the Brazilian state of Paraná (KANIESKI et al, 2012). Machado et al (2014) also found a weak correlation between rainfall and increment in diameter of Araucaria angustifolia (Bert.) O. Kuntze at R = 0.15 and a moderate correlation with the increment of Pinus taeda L. at R = 0.32, with both species in the initial phase.…”
Section: Narducci Ts Et Almentioning
confidence: 99%
“…Stape et al (1997), estimando produtividade de povoamentos híbridos de Eucalyptus grandis e Eucalyptus urophylla, concluíram que a produtividade é muito dependente da precipitação e que as características edáficas influenciavam na produtividade por meio da melhoria do aposte hídrico. MACHADO et al (2014), estudando o efeito de variáveis climáticas no crescimento de Pinus taeda e Araucaria angustifolia, observaram que os incrementos correntes médios (ICM'S) tiveram forte relação com temperatura, pressão atmosférica e fotoperíodo para ambas as espécies. A classe textural do solo foi classificada como franco arenoso para as camadas superficial e subsuperficial.…”
Section: Análise De Trilhaunclassified